Changes of Selected Behavior in High Producing Dairy Cows in the Time of Heat (Global Journal of Science Frontier Research, 2014)
Successful Artificial Insemination (AI) requires that humans detect the receptive phase of oestrus. There are various ways to detect oestrus in cattle, and behavior plays a key role in each method. The aim of this study was to detect different behaviors using time sampling method in 5-minute intervals and analyzed. Given over a period of 1 week (24 hours) in 34 dairy cows of LLFG Iden recorded these behaviors, in which 11 cows were observed in oestrus. The behavior has been differentiated as follows: feeding, resting and lying including rumination, standing on the walkways or the cubicles and standing rumination, including the duration of milking. The activities presented as percentages of the daily sum shows that the largest changes in the "standing" of the cows are observed. For standing in the time without oestrus 30 % of the day were used. In oestrus increased it to an average of 47 % of the day. The duration of the externally visible oestrus of cows averaged 944 minutes per day, with a very high variability could be determined.
Keywords: heat; dairy cows; behavior